2024
DOI: 10.1038/s41467-024-46244-5
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-temporal-spatial customization via modulating multimodal nonlinear pulse propagation

Tong Qiu,
Honghao Cao,
Kunzan Liu
et al.

Abstract: Multimode fibers (MMFs) are gaining renewed interest for nonlinear effects due to their high-dimensional spatiotemporal nonlinear dynamics and scalability for high power. High-brightness MMF sources with effective control of the nonlinear processes would offer possibilities in many areas from high-power fiber lasers, to bioimaging and chemical sensing, and to intriguing physics phenomena. Here we present a simple yet effective way of controlling nonlinear effects at high peak power levels. This is achieved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…a step-index (SI) or a graded index (GRIN) fiber. The modes of SI fibers have larger modal areas and more closely spaced propagation constants for the same numerical aperture, which leads to increased mode coupling and higher sensitivity to bending [39,59]. Thus, using an SI fiber allows more control per actuator, which may decrease the required amount of actuators.…”
Section: The Fibermentioning
confidence: 99%
See 1 more Smart Citation
“…a step-index (SI) or a graded index (GRIN) fiber. The modes of SI fibers have larger modal areas and more closely spaced propagation constants for the same numerical aperture, which leads to increased mode coupling and higher sensitivity to bending [39,59]. Thus, using an SI fiber allows more control per actuator, which may decrease the required amount of actuators.…”
Section: The Fibermentioning
confidence: 99%
“…Qiu et al have recently shown that one can resolve this challenge using a fiber piano [59,79]. The control of the wavefront was achieved during nonlinear light propagation in multimode fibers using a fiber piano that was built using 3D printing and low-cost stepper motors.…”
Section: Control Of Nonlinear Processes In Multimode Fibersmentioning
confidence: 99%